ANALISIS STRATEGI PENYELESAIAN WANPRESTASI DALAM PERJANJIAN KREDIT DENGAN JAMINAN PADA PT. PEGADAIAN KCP SUMBAWA BESAR - Usman, U; Wardi, Suharli (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the default resolution strategy in a credit agreement with collateral at PT. Pegadaian KCP Sumbawa Besar. This type of research was descriptive that aims to describe the default resolution strategy in credit agreement with collateral at PT. Pegadaian KCP Sumbawa Besar. The type of data used was qualitative data in the form of research informants' perceptions regarding research objects collected directly by researchers from the original source, namely research informants using interview techniques. The informants in this study consist of key informants and main informants. Key informants consist of employees of PT. Pegadaian KCP Sumbawa Besar who are directly related to the provision of pawn credit, totaling 5 people, while the main informants consist of pawn credit customers at PT. Pegadaian KCP Sumbawa Besar, totaling 5 people. Data analysis was carried out using qualitative analysis techniques proposed by Miles and Huberman, including data reduction, data display, and drawing conclusions/verification. The results of this study indicate that the strategy carried out by PT. Pegadaian KCP Sumbawa Besar to resolve defaults in credit agreements with collateral are through notification to customers, issuing warning letters, and confiscating collateral for auction. Considering that credit distribution is a risky activity, credit provision should be carried out by applying the principle of caution. Credit officers must be more careful in selecting prospective customers to minimize the occurrence of default and pay more attention to the value of the goods used as collateral so as not to cause losses if default occurs.